2021
DOI: 10.1037/rep0000374
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of deployment and nondeployment mild TBI on neuropsychological outcomes.

Abstract: Objective: Mild traumatic brain injury (TBI) that occurs in a deployment environment is characteristically different from mild TBI that occurs outside of deployment. This study evaluated differential and interaction effects of deployment and nondeployment mild TBI on cognitive and behavioral health outcomes. Research Method: Combat veterans (N ϭ 293) who passed performance-validity measures completed the Mid-Atlantic MIRECC Assessment of TBI (MMA-TBI), Clinician-Administered Posttraumatic Stress Disorder (PTSD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…58,66,67 Prior studies have shown that deployment-related TBI is associated with poorer TMT performance, even when compared to non-deployment TBI. 8 Altered asymmetry of the cingulum in our sample appeared to be primarily driven by deficits in the right cingulum, leading to an exaggerated laterality index. Lower FA of the left cingulum was linked with slower processing speed and set shifting, as measured by the TMT in the TBI group.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…58,66,67 Prior studies have shown that deployment-related TBI is associated with poorer TMT performance, even when compared to non-deployment TBI. 8 Altered asymmetry of the cingulum in our sample appeared to be primarily driven by deficits in the right cingulum, leading to an exaggerated laterality index. Lower FA of the left cingulum was linked with slower processing speed and set shifting, as measured by the TMT in the TBI group.…”
Section: Discussionmentioning
confidence: 64%
“…3 TBI occurring during deployment has been associated with a greater variety of outcomes than TBI sustained outside deployment. [4][5][6][7][8] Blast-related TBI in particular has been called the "signature injury" of post-9/11 conflicts (e.g., OEF/OIF/OND). Understanding brain structural changes and their relation to neurobehavioral sequelae following blast-related injuries, however, requires further elucidation as research on mTBI due to impact may not apply as the injury mechanisms differ.…”
Section: Introductionmentioning
confidence: 99%
“…Many individuals with pain may not recognize that the domains in the M2H model (Fig. 1 ) are relevant to the pain experience [ 10 , 28 35 ]. Helping persons with LBP understand the connections between holistic aspects of health and pain is foundational to the application of M2H as a strategy to manage chronic LBP.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that cognitive outcomes do not differ based solely on history of mTBI (Brenner et al, 2010;Verfaellie et al, 2014) but are rather associated with PTSD (Shandera- Ochsner et al, 2013;Storzbach et al, 2015;Verfaellie et al, 2014). Conversely, other research has reported that history of deployment TBI-but not current PTSD-may be associated with poorer cognitive functioning (Martindale et al, 2021). Given inconsistent findings regarding neuropsychological outcomes of comorbid mTBI and PTSD, additional research is warranted to further investigate these multifaceted relationships.…”
Section: Discussionmentioning
confidence: 99%
“…For example, individuals with both PTSD and TBI report more severe neurocognitive symptoms (Tanev et al, 2014). Moreover, both PTSD and deployment TBI have been linked to worse behavioral health outcomes (Martindale et al, 2018) and worse cognitive functioning (Martindale et al, 2021). However, less work has focused on the role of deployment TBI in PTSD recovery and in the relationship between PTSD and functional outcomes.…”
Section: Introductionmentioning
confidence: 99%